Effect of Depth of Sowing on Germination of Kail (Pinus wallichiana) Seed - Singh, R. V.; Chandra, J. P.; Sharma, S. N. (Indian Forester, 1973)
The results of the experiments conducted on the effect of depth of sowing on germination of kail seeds are reported. Sowings done up to 15 mllilmetres depth gave higher germination percentage than deeper sowings. Sowing of kail at a depth of 15 millimetres is recommended and sowing deeper than 25 millimetres should be avoided.